Preferências partidárias e classes sociais: o petismo é um fenômeno classista? - SOUSA, Marcos Felipe Rodrigues de (2020)
The discussion about party preferences in Brazil shows their low rates. Though, research reveals that the influence of the Workers’ Party (PT) on the partisanship of Brazilians elevates the country to the world average of party identification, ahead of countries like Germany, Spain, and Mexico. Historically, this party has been linked to an impoverished social stratum, the working class, social movements, and trade unions, as a result of its organization and partisan brand. Nevertheless, electoral strategies and pragmatic changes in the PT in recent years have brought it closer to different social classes. Analyses of social classes and their party preferences in Brazil have often associated them with economic income and this has resulted in a high aggregation of social class locations. In this way, I use an alternative measurement, through occupation in the labour market and education. I adapt a typology of hybrid social classes, with neo-weberian aspects, based on the EGP model, and, neo-marxist, based on the research of Santos (2005; 2010). Thus, I analyse petismo - the party preference for the PT - and its role in social classes, with a historical series from 2002 to 2018. I use data from CESOP/ Datafolha surveys in a table for four categories of social classes. In this typology, I elaborate descriptive data, molding the so-called “Thomsen index” in the differences in levels of partisanship between social classes, in the likelihood of a social class position showing party sympathy to the PT, against the likelihood of another social class position doing the same, standardizing from the natural logarithm of the odds ratio. I use a logistic regression model with the response variable to petismo. In addition to the social class, in this model I use the covariables of sex, age, education, region, and government evaluation. The descriptive results denote a greater party preference to the PT for the category of individuals in the service class, with 36.10% in 2002 and a minimum of 8.9% among entrepreneurs and professionals in 2018. Such values fluctuate, being the self-employed and precarious exposing greater petismo throughout the series. However, the alternative measurement of social classes to the usual of Brazilian political science to petismo, the application of the Thomsen index, and logistic regression confirmed the limits of the social class variable for party preferences to the PT. This research concludes that petismo was not a social class phenomenon, but with a moderate and relative social class partisanship, mainly for precarious sectors of society.